Projected changes in summer precipitation over East Asia with a high‐resolution atmospheric general circulation model during 21st century. (2nd September 2018) - Woo, Sumin; Singh, Gyan Prakash; Oh, Jai‐Ho; Lee, Kyoung‐Min
Abstract : We provide a broad view of East Asian summer monsoon (EASM) precipitation and their changes in the 21st century under the representative concentration pathway RCP4.5 and RCP8.5 scenarios using a high‐resolution (at 40 km) atmospheric general circulation model (AGCM). The simulated fields are validated against the multiple observational data sets in the reference period (1979–2008). Validation of seasonal simulated global climatology and EASM precipitation, annual cycle and various circulation fields including 25 individual Coupled Model Intercomparison Project phase 5 (CMIP5) and CMIP5 MME suggests that AGCM can be used to study the future projected characteristics of EASM. An investigation of uncertainty in precipitation shows larger values in the regions of high‐precipitation belt and low terrain. Future projections are categorized as near (2010–2039), mid (2040–2069) and far (2070–2100) futures. The model projects an increased summer precipitation of about 3.2% (2.3%) in near future, about 4.5% (4.5%) in mid‐future and about 2.4% (2.3%) in far future over East Asia region under RCP4.5 (RCP8.5) scenarios when compared to the reference period. As far as regional landmasses are concerned, model projects a gradual increase in the range of 5–15% over northeast China, coastal regions of southern China, Korea and Japan regions and a decrease of about 5–10% over southeastern and northwest parts of East Asia during the 21st century. The projected increase of EASM can be attributed to an increase in atmospheric moistures (relative humidity) over the east coast of China, Korea and northeast China and north and northwestwards enhancement of eddy geopotential height. Extreme events are examined by using various precipitation indices over EASM regions. Results indicate that the indices of heavy precipitation are projected to increase (both frequency and intensity) over Korea, Japan and northeast China in the range of 5–20%, indicating strong sensitivity of EASM to global warming. Abstract : Climatological JJA (June–August) mean precipitation (mm/day) during reference periods (1979–2008) over East Asian summer monsoon region in (a) CMIP5 MME, (b) GME, (c) GPCP, (f) APHRODITE, (d, e, g, h) seasonal biases (in %) from CMIP5 MME and GME with GPCP (APHTODITE). The contours show the 95% confidence level based on Student's t test.